Admission policies and methods at crossroads: a review of medical school admission policies and methods in seven Asian countries - Soemantri, D.; Karunathilake, I.M.; Yang, J.H.; Chang, S.C.; Lin, C.H.; Nadarajah, V.D.; Nishigori, H.; Samarasekera, D.D.; Lee, S.S.; Tanchoco, L.R.; Ponnamperuma, G. (Korean Journal of Medical Education, 2020)
Selecting the right applicants is an important part of medical student admission. While one universally accepted selection criterion is academic capacity, there are other criteria such as communication skills and local criteria (e.g., socio-cultural values) that are no less important. This article reviews the policies and methods of selection to medical schools in seven countries with varying socio-economic conditions and healthcare systems. Senior academics involved in medical education in Indonesia, Japan, Malaysia, the Philippines, Singapore, Sri Lanka, and Taiwan completed a pre-agreed pro-forma per each country to describe the country’s admission policies and methods. The details were then compared and contrasted. This review identifies tension between many of the policies and methods used in medical school admissions, such as between the need to assess non-cognitive abilities and widen access, and between the need for more medical professionals and the requirement to set high entry standards. Finding the right balance requires careful consideration of all variables, including the country’s human resource needs; socio-economic status; graduates’ expected competencies; and the school’s vision, mission, and availability of resources.
Keywords: Student selection; Medical students; Asians